2006
DOI: 10.1063/1.2335801
|View full text |Cite
|
Sign up to set email alerts
|

Exciton transitions in tetrapod-shaped CdTe nanocrystals investigated by photomodulated transmittance spectroscopy

Abstract: Articles you may be interested inImproved photovoltaic performance of bilayer heterojunction photovoltaic cells by triplet materials and tetrapodshaped colloidal nanocrystals doping Appl.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
8
0

Year Published

2008
2008
2014
2014

Publication Types

Select...
6
1

Relationship

4
3

Authors

Journals

citations
Cited by 10 publications
(9 citation statements)
references
References 35 publications
(17 reference statements)
1
8
0
Order By: Relevance
“…The first three confined states in the conduction and valence bands for sample A3 are shown in Figure 4. As in the case of all-CdTe tetrapods, 23 we found that, in the ground-state (GS) exciton, the electron density (Figure 4a) is mostly localized in the CdSe core region of the tetrapods, whereas the electron wave function spreads into the arms for the first excited state (1ES, Figure 4b), until it becomes completely delocalized into the arms for the second excited state (2ES, Figure 4c). On the other hand, the holes of the first three confined states are completely delocalized in the CdTe arms (Figure 4dÀf).…”
Section: ' Morphological Characterizationsupporting
confidence: 56%
“…The first three confined states in the conduction and valence bands for sample A3 are shown in Figure 4. As in the case of all-CdTe tetrapods, 23 we found that, in the ground-state (GS) exciton, the electron density (Figure 4a) is mostly localized in the CdSe core region of the tetrapods, whereas the electron wave function spreads into the arms for the first excited state (1ES, Figure 4b), until it becomes completely delocalized into the arms for the second excited state (2ES, Figure 4c). On the other hand, the holes of the first three confined states are completely delocalized in the CdTe arms (Figure 4dÀf).…”
Section: ' Morphological Characterizationsupporting
confidence: 56%
“…5 Besides sphericalshaped quantum dots ͑QDs͒, other materials with more exotic shapes and compositions have been fabricated and studied optically. 2,6,7 One of the most intriguing nanostructures is based on the growth of a CdS rodlike shell onto a spherical CdSe QD. [8][9][10] Previous studies 11,12 show that in such a system carriers might experience different types of localization, since the hole remains confined inside the CdSe dot, whereas the electron is completely delocalized throughout the CdS nanorod.…”
Section: Introductionmentioning
confidence: 99%
“…Gao and Wang grew CdS nanobelts by using a thermal evaporation method [21]. They used a CVD setup to grow CdS nanobelts via vapor-liquidsolid (VLS) by the assistance of gold as metal catalyst and vapor-solid (VS) Exciton Bohr radius 3 nm [11] 6 nm [12] 7.3 nm [13] Exciton binding energy 28 meV [14] 13 meV [15] 25 meV [16] Electron effective mass 0.25 m e [17] 0.45 m e [18] 0.095 m e [17] Table 9.1 Selective material parameters of CdEs [10]. (Continued) process.…”
Section: Thermal Evaporation Methods To Grow Cd-chalcogenide Nanocrystalsmentioning
confidence: 99%
“…16 Typical SEM, TEM, and HRTEM images of Bi-catalyzed (a-c) CdTe and (d-f) CdS nanowires. Reprinted with permission from Ref [38]…”
mentioning
confidence: 99%